Gynecologic and obstetric surgery : challenges and management options - Coomarasamy, Arri (Chichester, West Sussex ; Hoboken, NJ : John Wiley & Sons Inc., 2016)
'Obstetric and gynecologic surgery is a craft that requires sound knowledge and skills. The knowledge and skills will need to be applied to the specifics of each surgical patient to enable the best surgical management and minimize complications. This resource book offers insightful management options to many of the challenges a gynecologic or obstetric surgeon may face before, during or after an operation. Designed to guide the surgeon to safe practice throughout all stages of surgical management, it offers case studies, management options with tips and tricks, and ideas for prevention of complications. Key points and summaries are provided at the end of each chapter for'elevator reading', i.e., quick brushing up of facts on the way to facing a challenge. Divided into two sections the book first covers general pre, intra and post-operative challenges and, second, specific operative procedures within the specialist areas in obstetrics and gynecology'--Provided by publisher.
Witness patient 170 Termination of pregnancy at advanced gestation 171 Cervical fibroids: techniques for myomectomy and hysterectomy 172 Hysterectomy for broad ligament fibroids 173 Hysterectomy for a double uterus 174 Cervical stump excision 175 Surgery for ovarian remnant 176 Surgery for a missing intrauterine contraceptive device 177 Management of imperforate hymen, transverse and other vaginal septa 178 Benign lesions in the groin and vulva 179 Cystic structure in the upper vagina 180 Adnexal masses in infants and children 181 Nerve injuries associated with gynecologic and obstetric surgery 182 Consent challenges 183 Dealing with complaints 184 Dealing with litigation.
Includes bibliographical references and index.
Print version record.
Keywords: Generative organs, Female -- Surgery; MEDICAL -- Gynecology & Obstetrics; Generative organs, Female -- Surgery; Gynecologic Surgical Procedures; Obstetric Surgical Procedures; Urologic surgical procedures; Electronic books